Constructing a Modern Society Through "Depillarization". Understanding Post‐War History as Gradual Change1. Issue 3 (5th August 2014) - van Dam, Peter
Abstract The term "depillarization" ("ontzuiling") emerged in the Netherlands during the 1970s to proclaim the end of a society dominated by "pillarization" ("verzuiling"). In breaking away from the past, a groundbreaking renewal of religious and civic life through secularization and individualization was proclaimed or deplored. As hopes of an emancipation from the past subsided in the face of a considerable continuity, depillarization became a narrative of loss and frustration. This article shows how metaphors of disaggregation such as depillarization have produced an inability to conceptualize contemporary society, accompanied by a distortion of the past as the "other" of the present. It demonstrates how such metaphors may become dominant through their ability to incorporate competing visions of social order and the integration of scholarly and popular discourse. In conclusion, this article proposes to overcome the narratives of disaggregation by interpreting post‐war history as a gradual transformation from the ideals and practices of heavy communities to those of light communities in the domains of politics, civil society and religion.